Structure‐Based Design and Synthesis of Piperidinol‐Containing Molecules as New Mycobacterium abscessus Inhibitors. Issue 3 (20th March 2020) - de Ruyck, Jérôme; Dupont, Christian; Lamy, Elodie; Le Moigne, Vincent; Biot, Christophe; Guérardel, Yann; Herrmann, Jean‐Louis; Blaise, Mickaël; Grassin‐Delyle, Stanislas; Kremer, Laurent; Dubar, Faustine
Abstract: Non‐tuberculous mycobacterium (NTM) infections, such as those caused by Mycobacterium abscessus, are increasing globally. Due to their intrinsic drug resistance, M. abscessus pulmonary infections are often difficult to cure using standard chemotherapy. We previously demonstrated that a piperidinol derivative, named PIPD1, is an efficient molecule both against M. abscessus and Mycobacterium tuberculosis, the agent of tuberculosis, by targeting the mycolic acid transporter MmpL3. These results prompted us to design and synthesize a series of piperidinol derivatives and to determine the biological activity against M. abscessus . Structure‐activity relationship (SAR) studies pointed toward specific sites on the scaffold that can tolerate slight modifications. Overall, these results identified FMD‐88 as a new promising active analogue against M. abscessus . Also, we determined the pharmacokinetics properties of PIPD1 and showed that intraperitoneal administration of this compound resulted in promising serum concentration and an elimination half‐life of 3.2 hours. Abstract : Molecular modelling : Molecular representation of the interaction of PIPD1 and M. abscessus MmpL3 predictive model. On one side, PIPD1 is hydrogen‐bound to the carboxylic acid group of D618 through its amino moiety. On the other side, its hydroxyl group is H‐bound to the hydroxyl of Y219 and a potent interaction with the carboxylic acid group of D258 can occur. A stabilization occurred through π‐π interactions between the toluene moiety of PIPD1 and phenyl rings of F262 and F622.